The Status of Homestead Poultry Production in Sylhet Region - Khan, M.M.H.; Miah, M.Y.; Bhuiyan, M.M.; Begum, S.; Hussain, M.M.; Khanum, R. (International Journal of Poultry Science, 2006)
Local chickens dominate poultry production in Bangladesh. For this reason, an investigation was conducted to determine the existing production system and production performance of native chicken in the Sylhet areas of Bangladesh. Data were collected from 180 households of 6 villages of Sylhet district in Bangladesh. In Sylhet mainly poor families, who have arrived from outside and are landless rear poultry. Most of the households (58.33%) had 0-15 chicken. Most of the families (75%) reared their chicken in combined house with duck. Materials used for housing were similar to other parts of the country. Mainly female members were involved in poultry rearing. About fifty percent farmers got on an average less than 70 eggs per year per bird. A few farmers (5.56%) informed that they had collected more than 130 eggs from a bird in a year. In most of the cases (47.22%) the length of clutch was less than 20. Interval between two clutches was found in highest percentage(42.22%). Highest egg production was observed in winter season (52.78%) followed by summer, spring and late autumn. Maximum (60%) farmer had vaccinated their birds and 55% farmers got service from Department of Livestock Services.